Effect of Red Cabbage Juice as a Hepatoprotector on Liver Enzyme Levels - Andina Putri Aulia; Hesty Wahyuningsih (Borneo Journal of Medical Laboratory Technology, 2021)
Background: Anthocyanin-rich red cabbage is known to reduce hepatic enzymes levels such as SGPT, SGOT, ALP, and GGT in drug-induced liver injury (DILI). Objective: This study aimed to determine the effect of red cabbage juice on SGOT, ALP, and GGT levels in acetaminophen-induced liver injury in rats.Methods: This was an experimental study using a post-test-only control group design. Thirty male Wistar rats were randomly divided into 5 groups. K1 was the negative control. K2, K3, K4, and K5 were pretreated with 300 mg acetaminophen. K3, K4, and K5 were treated with 0.5 g/ml of red cabbage juice, 0.7 g/ml of red cabbage juice, and 0.9 g/ml of red cabbage juice respectively. Data were analyzed using one-way ANOVA and post hoc LSD (p<0.05). Results: There was no significant difference in SGOT and GGT levels among the groups p=0.271(p>0.05) and p=0.053 (p>0.05) respectively. Whereas ALP levels showed significant differences among the groups p=0.000 (p<0,05) respectively. Conclusion: The administration of red cabbage in any dose had no effect on SGOT and GGT levels in acetaminophen-induced liver injury in rats whereas in ALP, the most effective dose to cause an effect is 0.5 g/ml.